2008
DOI: 10.3200/jach.56.5.505-512
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure During Physically Interactive Video Game Playing in Male College Students With Different Playing Experience

Abstract: Participants with greater playing experience can work at higher intensities, promoting greater energy expenditure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 28 publications
(29 reference statements)
1
95
1
5
Order By: Relevance
“…18 Facilitators of exergames (ie, social support, competition, music, experience, new consoles, multiple player modes, contact with players in separate rooms, contact via Internet) hold promise in sustaining exergaming. 34,38,39,42 Replication of these results is warranted to determine if exergaming is a promising PA alternative for girls, as well as to investigate other potential correlates of exergaming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Facilitators of exergames (ie, social support, competition, music, experience, new consoles, multiple player modes, contact with players in separate rooms, contact via Internet) hold promise in sustaining exergaming. 34,38,39,42 Replication of these results is warranted to determine if exergaming is a promising PA alternative for girls, as well as to investigate other potential correlates of exergaming.…”
Section: Discussionmentioning
confidence: 99%
“…29 The primary purpose of extant exergaming studies has been to describe energy expended during exergaming. 12, 16,17,23,24,26,[30][31][32][33][34][35][36][37] Several studies also examine maintenance of exergaming over time, [38][39][40][41][42] and at least 3 small 43 and 1 large trial 44 evaluate exergaming as a method to increase PA in youth. Two of the 3 small trials indicated modest improvements in PA, and the large longer trial suggested that exergaming leads to small but statistically significant decreases in BMI as well as improvements in body composition in overweight children.…”
mentioning
confidence: 99%
“…Greater playing experience allowed these participants to work at higher intensities, thereby promoting greater EE. For example, an experienced player with a mass of 68 kg would expend, on average, an additional 102 kCal per 30-minute session compared with an inexperienced player of the same mass [23]. Norlin et al reported an increase in HR maximum percent, VO 2 maximum percent, and RPE with increasing difficulty in gameplay mode [24].…”
Section: Energy Expenditure Associated With Dance Dance Revolutionmentioning
confidence: 99%
“…However, Wii Tennis was played in these studies rather than the more active Wii Boxing. Sell et al compared experienced with inexperienced DDR players [23]. Greater playing experience allowed these participants to work at higher intensities, thereby promoting greater EE.…”
Section: Energy Expenditure Associated With Dance Dance Revolutionmentioning
confidence: 99%
“…(Graves et al, 2007(Graves et al, , 2008Maddison et al, 2007;Ni Mhurchu et al, 2008;Ridley and Olds, 2008;Straker and Abbott, 2007). However, only a few studies on interactive game play as a physical activity have been performed with young-adults (Segal and Dietz, 1991;Sell et al, 2008;Tan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%